Encefalopatia hepática: relatório da 1º reunião monotemática da Sociedade Brasileira de Hepatologia - Bittencourt, Paulo Lisboa; Strauss, Edna; Terra, Carlos; Alvares-da-Silva, Mario Reis; Martinelli, Ana de Lourdes C.; Mattos, Angelo Alves de; Campos, Antonio Carlos; Santos, Bento Cardoso dos; Oliveira, Cacilda Pedrosa de; Marroni, Caroline Possa; Lobato, Cirley Maria de Oliveira; Marroni, Cláudio Augusto; et al. (My University, 2011)
Hepatic encephalopathy (HE) is a functional disorder of the central nervous system (CNS) associated with liver failure, either end-stage chronic liver disease or fulminant hepatic failure. Its pathogenesis remains complex and poorly understood. In view of recent advances in the management of HE, the Brazilian Society of Hepatology endorsed a monothematic meeting regarding HE in order to gather experts in the field to discuss related data and to draw evidence-based recommendations concerning: management of HE and intracranial hypertension in FHF, treatment of episodic HE in cirrhosis, controversies in the management of EH including difficult to treat cases and diagnostic and treatment challenges for minimal HE. The purpose of this review is to summarize the lectures and recommendations made by the panel of experts of the Brazilian Society of Hepatology.

A encefalopatia hepática (EH) é um distúrbio funcional do sistema nervoso central (SNC) associado à insuficiência hepática, de fisiopatologia multifatorial e complexa. Devido aos avanços no conhecimento sobre o manejo da EH na cirrose e na insuficiência hepática aguda (IHA), a diretoria da Sociedade Brasileira de Hepatologia (SBH) promoveu uma reunião monotemática acerca da fisiopatologia, diagnóstico e tratamento da EH, abordando aspectos controversos relacionados ao tema. Com a utilização de sistemática da medicina baseada em evidências, foram abordados o manejo da EH e da hipertensão intracraniana na IHA, o manejo da EH episódica na cirrose, as controvérsias no manejo da EH e a abordagem da EH mínima. O objetivo desta revisão é resumir os principais tópicos discutidos na reunião monotemática e apresentar recomendações sobre o manejo da síndrome votadas pelo painel de expertos da SBH.
Hepatic encephalopathy: report of the 1st monothematic meeting of the Brazilian Society
Keywords: Hepatic encephalopathy; Cirrhosis; Fulminant hepatic failure; Portal hypertension; Liver transplantation; Encefalopatia hepática; Cirrose; Insuficiência hepática aguda; Hipertensão portal; Transplante de fígado